Sobolev-type Fractional Stochastic Differential Equations Driven by Fractional Brownian Motion with Non-Lipschitz Coefficients (Journal of Partial Differential Equations, 2019)
In this paper, we are concerned with the existence and uniqueness of mildsolution for a class of nonlinear fractional Sobolev-type stochastic differential equationsdriven by fractional Brownian motion with Hurst parameter H∈(1/2,1) in Hilbertspace. We obtain the required result by using semigroup theory, stochastic analysisprinciple, fractional calculus and Picard iteration techniques with some non-Lipschitzconditions.